Modeling saltwater intrusion in Sibunag River Basin, coastal aquifer of Guimaras Island, Philippines using a coupled SWAT-SEAWAT model - Doung, Ratha; Blanco, Ariel C. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
Salinity intrusion is one of the major threats to freshwater resources. The impact of this is most severe in small islands where the main source of freshwater is groundwater. The Island Province of Guimaras, located in the Region 6 of the Philippines, consists of five municipalities namely Suclaran, Sabang, Cabalagnan, Tando, and Zaldivar. The island has a population of 162,943 based on the 2010 census, giving a population density of about 270 individuals per sq.km. Groundwater is the main source of freshwater supply in the entire island area. Nowadays, the abstraction rate of groundwater is increasing dramatically to meet the freshwater demand for agriculture and domestic uses. Consequently, the area is believed to be faced with many problems such as groundwater pollution, especially saline water intrusion. The objective of this research is to characterize and understand the groundwater and surface water systems in order to assess salinity intrusion and its impacts on the coastal aquifers of Guimaras Island, Philippines. This research aimed to model the system of surface water and groundwater in order to evaluate the degree of salinity in freshwater at coastal zone of the site under current and future groundwater abstraction rates and sea level rise. The research is implemented using the following numerical models: MODFLOW and SeaWAT supported by the Groundwater Modeling System (GMS) and the Soil and Water Assessment Tool (SWAT) model. Hydrological and hydrogeological data such as rainfall, temperature, evapotranspiration, humidity, wind speed, sun radiation, hydraulic conductivity, land use, land slope, and soil properties have been collected and used as data inputs. Furthermore, the coupled use of the models was meant to simulate groundwater now patterns, river basin hydrology, and assess the impact of saltwater intrusion at the present time and predict its potential effects in the future considering different scenarios. Groundwater now pattern modeling for the entire island was implemented and calibrated based on actual field surveys and monitoring. The system is considered an unconfined aquifer system where the aquifer thickness varies up to 100 meters. A recharge rate equals to 0.0004 m/day was calculated based on the density of rainfall and average annual air temperature during 37 years (1975-2011). Pumping tests were conducted at 8 selected locations of the study site in order to calculate hydraulic conductivity values. Conductivity from test wells equaled to 2.637 mm/day and 1.882 mm/day for maximum and minimum value respectively. Compared to observed measured head from 20 of dug wells, groundwater flow modeling has been carried out with a Root Mean Squared Error (RMSE) of 0.988 and a Relative Root Mean Squared Error (RRMSE) of 7.983%. The head of groundwater computed from groundwater model agreed with the head of groundwater computed from the data provided by the Local Water Use administration. The results revealed that the groundwater flow pattern starts from high hydraulic head (Hmax=224m) at the central to the coastlines (Hmin=O m) of Guimaras Island. Transient modeling showed groundwater head variation at different time step based on recharge rate variations derived from rainfall density. The simulation was set at daily time step and processes and conditions were simulated from Mar 11, 2012 to June 23, 2013. Transient head was calibrated using monitoring data at five different wells at the coasts. Absolute root mean square errors of 0.92%, 0.87%, 0.69%, 0.64%, and 0.88% for the monitoring wells located in the Northwestern, Northeastern, Southwestern, Southeastern and Southern coasts of the island, respectively. Transient head computed by the model indicated the sensitiveness to rainfall value more than observed data. Hydrological modeling was conducted using digital elevation model data, soil characteristics, land use data, and slope classification. Recharge rate increased from 10.93% of rainfall value calculated by empirical method to 17.26% of rainfall value calculated by hydrological model. SEAWAT was used to model saltwater intrusion in the study site. Based on actual household location, household size, and current groundwater abstraction rate at present time, degree of groundwater water salinity in aquifer showed that there are 58 wells where water is already salty and 103 wells located close to the sea contained brackish water. Likewise, the number of salinity-polluted wells would increase in 2030, 2050, and 2010, when pumping rate is increased. For scenario 1 in 2030, scenario 2 in 2050, and scenario 3 in 2100, the salinity degree of around 35 ppt will be experienced in 67 wells, 138 wells, and 242 wells, respectively. These huge numbers of salinity-polluted wells would cause serious impacts on households if alternative freshwater supplies such as river water and rain water are not tapped to address the growing demand for water resource.
Thesis (Ph.D. Environmental Engineering)--University of the Philippines Diliman
Keywords: Groundwater -- Philippines -- Guimaras; Saltwater encroachment -- Philippines -- Guimaras; Aquifers -- Philippines -- Guimaras; Hydrogeology -- Philippines -- Guimaras